Criminal investigation - Charles R. Swanson (McGraw-Hill, 2006)
Widely recognized as the most accurate and comprehensive text in the field, this practical, step-by-step introduction to criminal investigation gives students a logical framework for understanding the investigative process. Major sections cover current issues such as environmental crime, the looting of archaeological sites, videotaping of crime scenes, street gangs, and drugs. Case studies throughout the text emphasize the applied technique of criminal investigation, and its consistently praised art program including graphs, charts, and arresting photographs, depict the practical aspects of investigation and help to clarify difficult scientific concepts. The free simulation CD gives students a series of interactive modules covering key aspects of criminal investigation. The PowerWeb passcard lets students access important contemporary articles about criminal justice from both the popular press and journals